In vitro evaluation of adhesion and aggregation abilities of four potential probiotic strains isolated from guppy (Poecilia reticulata) - Balakrishna,Aparna (2013)
The aim of this work was to study the probiotic-related characteristics of four strains of bacteria isolated from the normal flora of the guppy, Poecilia reticulata. In vitro results showed that the strains, namely, MBTU_PB1, MBTU_PB2, MBTU_PB3 and MBTU_PB4 had higher adhesion abilities than the tested indicator strains. However, an association between the cell-surface hydrophobicity and the ability to adhere to the intestinal mucus was not observed for these strains. Further, the selected strains were strongly autoaggregating (autoaggregation percentage ≥ 80) and also showed strain-specific coaggregation abilities with the tested indicator strains.